A Review on Integrating Bioinformatics Tools in Modern Plant Breeding - , Vangapandu Thriveni, Jatin Teotia, Somak Hazra, Thounaojam Bharti, Manoj Kumar, Michelle C. Lallawmkimi, Deepak Panwar (Archives of Current Research International, 2024)
Bioinformatics has become integral to modern plant breeding, facilitating the analysis of large-scale genomic data, identifying key genetic markers, and enabling precision breeding techniques such as genomic selection. Advances in sequencing technologies and computational tools have accelerated the pace of crop improvement, allowing for the rapid identification of genes associated with important agronomic traits, including yield, stress tolerance, and disease resistance. The integration of bioinformatics in plant breeding also presents significant challenges, particularly in terms of data management, multi-omics integration, and the interpretation and validation of complex datasets. The role of emerging trends such as pangenomics, metagenomics, and epigenomics in expanding the scope of plant breeding, as well as the increasing importance of artificial intelligence and machine learning in enhancing predictive accuracy and optimizing breeding strategies. Personalized plant breeding and precision agriculture are identified as promising approaches for tailoring crop varieties to specific environments and farming practices, driven by bioinformatics tools that enable detailed analysis of genomic and phenotypic data. Ethical considerations and data privacy issues are also addressed, emphasizing the need for transparent and equitable practices in the collection, sharing, and use of genomic data. The importance of collaborative efforts and global initiatives in advancing bioinformatics-driven plant breeding, with a focus on fostering international cooperation, building capacity in developing regions, and ensuring open access to bioinformatics resources. As the field continues to evolve, bioinformatics will play a Important role in developing sustainable agricultural systems capable of meeting the demands of a growing global population while mitigating the impacts of climate change. The current applications, challenges, and future prospects of bioinformatics in plant breeding, offering insights into the critical role of this field in shaping the future of agriculture.